PROLONGED DISPERSION OF QT AND QTC IN THALASSEMIA MAJOR PATIENTS - A. Kocharian; M.Dalir Rooyfard R. Aghanouri (Acta Medica Iranica, 2003)
Thalassemia major patients require repeated transfusions of packed cell and their lysis lead to iron deposition especially in the cardiac walls such as septum and posterior wall, so make thickening and cause cardiac disorders. In this case-control study, our object was to appoint if QT and QTC and Te dispersions were predictors of cardiac disorders in thalassemia major patients or not. 34 thalassemic patients who had no cardiac sign or symptom and 34 normal subjects between 16-18 years old of age were referred for evaluation of their QT, QTC, and Te dispersions in their ECGs. All standard 12-lead ECGs were obtained from them and were digitized by a single observer blinded to the assigned groups. As references, QT and Te were measured and QTC was calculated by Bazett,s formula.Results showed highly significant differences in QT and QTC dispersions between thalassemic patients and control group (P-value = 0.004 and 0.001 respectively); but it was moderate for Te (P-value = 0.086). About the means of QT, QTC and Te, there were highly significant differences between two groups too (P-value = 0.001, 0.000, and 0.000 respectively). QT and QTC dispersions are significantly higher in thalassemic patients than normal persons and may be predictors of cardiac disorders such as arrhythmias or sudden death in thalassemic patients in future.